Sons benefit from paternal care in African striped mice. Issue 4 (23rd October 2020) - Pillay, Neville; Rymer, Tasmin L.
Abstract: Mammalian paternal care is rare and is often linked to enhanced fitness under particular ecological conditions. The proximate consequences of paternal care on offspring are lacking, however. Here, we tested whether levels of paternal care predict the behavioural, cognitive and physiological development of sons in the naturally paternal African striped mouse ( Rhabdomys pumilio ). We focused on sons raised in two treatments: biparental (both parents) or uniparental (mother alone) families. We recorded levels of interactions between pups with both parents, and later assessed the behaviour, cognition and physiology of sons at three developmental stages: juvenile, sub‐adult and adult (sexual maturity). Sons from biparental families showed (a) reduced anxiety as juveniles; (b) greater exploration and social interaction at different stages; (c) better cognition; and (d) reduced corticosterone concentrations than sons from uniparental families. In contrast, sons from uniparental families showed greater levels of paternal care, although prolactin concentrations did not differ between treatments. Paternal care in striped mice enhances fitness of males. Here, we also show that sons benefit psychologically and physiologically through interactions with their fathers. However, sons also trade‐off such benefits against their own paternal care behaviour, suggesting that fathers influence the development of their son's phenotype in complex ways.